Tail Bud Progenitor Activity Relies on a Network Comprising Gdf11, Lin28, and Hox13 Genes - Aires, Rita (2019)
During the trunk-to-tail transition, axial progenitors relocate from the epiblast to the tail bud. Here, we show that this process entails a major regulatory switch, bringing tail bud progenitors under Gdf11 signaling control. Gdf11 mutant embryos have an increased number of such progenitors that favor neural differentiation routes, resulting in a dramatic expansion of the neural tube. Moreover, inhibition of Gdf11 signaling recovers the proliferation ability of these progenitors when cultured in vitro. Tail bud progenitor growth is independent of Oct4, relying instead on Lin28 activity. Gdf11 signaling eventually activates Hox genes of paralog group 13, which halt expansion of these progenitors, at least in part, by down-regulating Lin28 genes. Our results uncover a genetic network involving Gdf11, Lin28, and Hox13 genes controlling axial progenitor activity in the tail bud.